KEDUDUKAN PERJANJIAN PERKAWINAN DALAM KITAB UNDANG-UNDANG HUKUM PERDATA - Karman Karman (Cross-border, 2020)
The position of the marriage agreement which is held in each region in this country is according to the Marriage Law no. 1 of 1974 article 29, which states that a marriage agreement is an agreement that regulates the consequences of a marriage bond. In Indonesia, marriage agreements are allowed to be made and implemented since the enactment of the Civil Code. The marriage agreement in article 29 does not only regulate the issue of property and the consequences of marriage, but also includes the rights/obligations that must be fulfilled by both parties as long as the agreement does not conflict with legal, religious and moral boundaries. The arrangement of the agreement in marriage is explained in Chapter VII articles 139 -154, in this case the important point is that the marriage agreement is valid and binding on the parties/bride in marriage. In this study it was found that the position of the agreement in marriage according to the Civil Code is an agreement made by a prospective husband and wife before the marriage takes place, containing the consequences of marriage on assets that have three types of agreements, namely togetherness of profit and loss, togetherness of results and the elimination of togetherness of property. The marriage agreement is made by a notary and its contents cannot be changed.